2020
DOI: 10.1021/acs.jpclett.0c00999
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Molecular Simulation-Based Predictions of koff Values: A Metadynamics Study

Abstract: The k off values of ligands unbinding to proteins are key parameters for drug discovery. Their predictions based on molecular simulation may under- or overestimate experiment in a system- and/or technique-dependent way. Here we use an established methodinfrequent metadynamics, based on the AMBER force fieldto compute the k off of the ligand iperoxo (in clinical use) targeting the muscarinic receptor M2. The ligand charges are calculated by either (i) the Amber standard procedure or (ii) B3LYP-DFT. The calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 64 publications
3
72
0
Order By: Relevance
“…The second key issue is the quality of the interatomic potential. Standard biomolecular force‐fields, widely used in CSBDD, are parametrized to reproduce a subset of experimental data, necessarily limiting their domain of applicability 34 . They neglect polarization effects and charge transfer, which may play a role in ligand/target interactions 34 .…”
Section: Hpc: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second key issue is the quality of the interatomic potential. Standard biomolecular force‐fields, widely used in CSBDD, are parametrized to reproduce a subset of experimental data, necessarily limiting their domain of applicability 34 . They neglect polarization effects and charge transfer, which may play a role in ligand/target interactions 34 .…”
Section: Hpc: Applicationsmentioning
confidence: 99%
“…It can routinely run systems of 10 5 atoms for μs timescales. MD‐based ligand binding free energies 13,28–32 allow to predict potency and residence times of drugs 30,33–35 . Examples of the impact of MD in pharmacology include (but are by no means limited to) the development of the FDA‐approved HIV‐1 lifesaving drugs nelfinavir and raltegravir, 36 the ongoing SARS‐CoV‐2 research 37–40 and the development of a variety of anti‐cancer drugs 41,42 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In metadynamics bias potentials are deposited along chosen collective variables to overcome free energy barriers. As such metadynamics is an efficient method for exploring protein-ligand unbinding kinetics, [26][27][28][29] bridging the microsecond simulation and the second-to-minute experimental timescales. Most recently, metadynamics simulations of morphine and buprenorphine dissociation from mOR showed that the ligand transitioned to the vestibule region after the D147 3.32 salt bridge was disrupted.…”
Section: Introductionmentioning
confidence: 99%